Migration as personal transition - Van Tonder, Chris (Elsevier BV, 2013)
Although acculturation is the preferred interpretation frame in migration research, it fails to fully accoun t for the entire migration experience. The current study aimed to establish whether ‘personal transition’ per definition (Van Tonder, 2004) can be discerned from the ‘migration stories’ of research participants. Data were obtained from 21 South African migrants to Australia, using semi-structured phenomenological interviews. ‘Migration’ is revealed as a challenging, multifaceted and protracted change process, consistent with the personal transition curve. Viewing migration as ‘change’ enables a broadened perspective beyond the conceptual boundaries of acculturation and implies an extended intervention repertoire for assisting migrants.